Analisis Faktor yang Mempengaruhi Peningkatan Serum Transaminase pada Pasien Demam Dengue di RSUD Ngudi Waluyo Wlingi pada Tahun 2023-2024 - Wijayanto, Fajar; Insanitaqwa, Aleyda (Jurnal Klinik dan Riset Kesehatan, 2024)
Background: Dengue fever has become a global and national health concern due to its increasing incidence rate over the past six years. Dengue infection may present with variable sign and symptoms. Major organ involvement may occur, including liver, which is characterized by an elevated transaminase serum level. Aim: This study aims to identify factors contributing to increased transaminase serum levels in patients with dengue fever at Ngudi Waluyo Wlingi General Hospital between 2023-2024. Methods: One hundred and sixty-nine patients with positive dengue serology admitted to Ngudi Waluyo Wlingi General Hospital from January 1st, 2023 to May 19th, 2024, were reviewed retrospectively. Only patients aged 15 years and over with complete laboratory data were included in this retrospective cross-sectional study, using total sampling approach. We collected demographic and laboratory data from electronic medical records, then analyzed and correlated the data with liver function values. Results: Increased AST levels was observed in 70 patients (41.4%), while ALT values was elevated in 32 patients (24.9%). This increase was significantly linked to decreased platelet counts (p=0). Additionally, age was statistically associated with ALT levels (p=0.022), while gender was significantly related to AST levels (p=0.04). However, leukocyte levels and dengue serology showed no significant correlation with serum transaminase levels (p>0.05). Together, dengue serology, platelet counts, leukocyte levels, gender, and age collectively have a significant effect on AST (14.3%) and ALT (13.6%) values. Among these factors, platelet counts exerted the greatest influence on AST and ALT levels. Conclusion: Elevated transaminase serum levels may occur in patients with dengue fever. This is associated with platelet counts, age, and gender. Therefore, diagnosing dengue infection should prompt measurement of liver function to ensure appropriate management according to each patient’s condition.